PENGEMBANGAN MEDIA PEMBELAJARAN VIDEO ANIMASI BERBANTUAN ARTIFICIAL INTELLIGENCE (AI) UNTUK MAHASISWA PIAUD IAIN CURUP - Meri Hartati; Aulia Rahmasari (CV. Kalimasada Group, 2025)
The purpose of this study is to produce prospective Early Childhood Education teachers, PIAUD Study Program IAIN Curup in providing various courses have good educational science insights and are creative in making learning media for early childhood. This study uses Development (R&D) with the ADDIE approach, which includes 5 stages: (1) Analysis stage, (2) Product design stage, (3) Product development, (4) Feasibility test stage, and (5) Evaluation stage. The results of this study are animated videos of early childhood social and emotional development teaching materials integrated with Islamic values. This teaching material received a very positive response and was considered very suitable for use. This is evidenced by the results of validation by experts (material experts, language experts, and media experts) who obtained an average score of 89% with the category